Penyuluhan Pencegahan Penularan Covid-19 bagi Ibu Hamil di Desa Padangsambian Kaja Denpasar Utara Bali - Ni Made Darmiyanti; Maria Gabriela Yuniati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service aims to provide education on how to prevent transmission of Covid-19 transmission for pregnant women in Padangasambian Kaja Village. The method carried out in this service is to provide counseling directly to pregnant women who come to posyandu. Instruments of this activity use leaflets and are analyzed descriptively.Â The results of this service activity have helped pregnant women to prevent the transmission of Covid-19 during this pandemic, with the help of leaflets about Covid-19 so that the education provided can be applied at home and the surrounding environment.